Comparative Evaluation of Voids Present in Conventional and Capsulated Glass Ionomer Cements Using Two Different Conditioners: An In Vitro Study - Mamta Kaushik; Roshni Sharma; Pallavi Reddy; Pallavi Pathak; Pooja Udameshi; Narmatha Vallakuruchi Jayabal (International Journal of Biomaterials)
This in vitro study evaluated the presence of voids in powder-liquid and capsulated glass ionomer cement. 40 cavities were prepared on root surfaces of maxillary incisors and divided into four groups. Cavities were conditioned with glass ionomer cement liquid (GC Corporation, Tokyo, Japan) in Groups 1 and 3 and with dentin conditioner (GC Corporation, Tokyo, Japan) in Groups 2 and 4. Conventional powder-liquid glass ionomer cement (GC Fuji II, GC Corporation, Tokyo, Japan) was used as a restorative material in Groups 1 and 2. Capsulated glass ionomer cement (GC Fuji II, GC Corporation, Tokyo, Japan) was used in Groups 3 and 4. Samples were sectioned and viewed under stereomicroscope to check for the presence of voids within the cement and at the cement-tooth junction. Data was analyzed using one-way ANOVA and Tukey’s post hoc tests. Group 4 showed statistically significant results (P<0.05) when compared to Groups 1 and 2 for voids within the cement. However, for voids at the margins, the results were statistically insignificant.